GAMBARAN KECANDUAN GAME ONLINE DAN MOTIVASI BELAJAR PADA SISWA KELAS XI DI SMA DELI MURNI DELITUA TAHUN 2022 - Mestiana Br. Karo,; Rotua Elvina Pakpahan ,; Kristin M Sihombing , (Jurnal Cakrawala Ilmiah, 2023)
Learning motivation is the overall driving force of a person's self that causes learning activities that guarantee learning activities and provide direction to learning activities so that the desired goals can be achieved. Online game addiction is a behavioral pattern of playing online games (digital games and video games) with several indications such as; can't control the urge to play the game. Online games can make students lazy to study and forget about daily activities This study aims to determine the description of online game addiction and learning motivation on students class XI of Deli Murni Delitua high school 2022. This type of research uses descriptive research. The sampling technique in this study uses a total sampling of 148 respondents. The instrument used was a questionnaire on Online Game Addiction and Learning Motivation. The results showed that most of the students who have severe online game addiction (71.6%), and mild (1.4%) and low learning motivation (62.8%) and high learning motivation (37.2%). These results indicate that students class XI of SMA Deli Murni Delitua are addicted to heavy online games and have low learning motivation.